Controlling Factors of Cell Design on Large-Format Li-Ion Battery Safety during Nail Penetration - Wang, Qing; Shaffer, Christian Edward; Sinha, Puneet K. (Frontiers in Energy Research, 2015)
In this paper we investigate the controlling design parameters of large-format Li-ion batteries on safety while undergoing nail penetration. We have identified three critical design parameters that control the safety during the nail penetration process: nail diameter, single sheet foil area, and cell capacity.Using commercial AutoLion software, we have investigated two typical design problems related to the selection of cell thickness and aspect ratio, namely: (1) the safety ramifications of increasing cell capacity via greater cell thickness for a fixed footprint, and (2) the effect of aspect ratio, or single sheet foil size, on safety at a given capacity. For a fixed footprint, our results indicate that the safety of the cell can be predicted by (Qcell Dnail^-0.5). For a given cell capacity, our results indicate that typically a larger single sheet foil area leads to a greater likelihood for thermal runaway due to its effect of making the heating more local in nature; however, for small cells ( 5Ah) and large nails ( 20mm), the greater aspect ratio can lead to a safer cell, as the greater surface area strongly cools the global heating of the cell.